2021
DOI: 10.1590/1518-8345.3844.3395
|View full text |Cite
|
Sign up to set email alerts
|

Social relationships and survival in the older adult cohort

Abstract: Objective: to verify the influence of social relations on the survival of older adults living in southern Brazil. Method: a cohort study (2008 and 2016/17), conducted with 1,593 individuals aged 60 years old or over, in individual interviews. The outcomes of social relations and survival were verified by Multiple Correspondence Analysis, which guided the proposal of an explanatory matrix for social relations, the analysis of survival by Kaplan-Meier, and the multivariate analysis by Cox regression to verify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
(44 reference statements)
0
7
0
3
Order By: Relevance
“…Researchers have emphasized the importance of relationships for quality of life in aging by stating that social interaction can promote the exchange of feelings capable of enhancing or mitigating the offer and receipt of assistance related to health maintenance ( Soares et al, 2021 ). Conversely, negative social interaction and interpersonal conflict often have a great impact on older adults’ psychological well-being ( Hupkens et al, 2018 ; Lee et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have emphasized the importance of relationships for quality of life in aging by stating that social interaction can promote the exchange of feelings capable of enhancing or mitigating the offer and receipt of assistance related to health maintenance ( Soares et al, 2021 ). Conversely, negative social interaction and interpersonal conflict often have a great impact on older adults’ psychological well-being ( Hupkens et al, 2018 ; Lee et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the structural aspects of social relationships, De Brito et al (2017) found that people with a relatively wide social network (i.e., nine or more people) had less risk of dying. Soares et al (2021) found that people with social interactions beyond the household—going outside and attending parties—were more likely to survive. In addition, Santini et al (2015) showed the importance of the size of the social network as well as its features.…”
Section: Discussionmentioning
confidence: 99%
“…In the Latin American context, small social networks (fewer than nine members [de Brito et al, 2017]) and a lack of diversity of social networks can be detrimental to the survival of older people, particularly when the network is confined to the family, although not when it is diversified (Santini et al, 2015). Conversely, social interaction beyond the household protects against mortality risk (Soares et al, 2021). The current panorama underscores the need to generate evidence in a country like Mexico, with distinctive features of strong and close ties among the elderly and their relatives, friends, and other members of the community, all of which represents a source of coexistence and support (Fuller-Iglesias & Antonucci, 2016; Guzmán et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…No Sul do Brasil, um estudo sobre as influências das relações sociais na sobrevivência dos idosos, mostrou que as interações sociais fortalecidas são marcadores de sobrevivência, portanto, a solidão é um preditor de mortalidade para esse grupo (21) .…”
Section: Discussionunclassified